(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The use of new technologies in the language lesson, the lesson of speech development allows the instructors to activate the cognitive interests of students, control the activities of each, significantly increase the pace of work, solve several problems at once: study new material, consolidate, performing practical work, including different types of exercises, deepen knowledge, conduct the control. It is very important that students work with passion at any stage of the lesson, and this maintains interest in the subject as a whole. This article discusses programs and methods for the formation of speech competencies in language lessons and their further improvements.